2018
DOI: 10.3311/ppch.12076
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Fluoride Removal from Groundwater

Abstract: Most of the arid and semiarid zones of the Indian subcontinent are seriously affected by the fluorosis problem due to high concentration of the fluoride in ground water. Due to leaching of fluoride from the fluoride bearing rocks, the groundwater gets contaminated with fluoride. The different techniques for fluoride removal namely, the Activated alumina, the Nalgonda technique, bone charcoal, contact precipitation, electro-dialysis, reverse osmosis, ion-exchange, clay column, bio-adsorbents and MgO are discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 46 publications
(48 reference statements)
1
2
0
Order By: Relevance
“…Cement has calcium oxide and fluoride reacted with calcium to give calcium fluoride minerals. Similar studies are reported by earlier researchers where the potential of minerals such as CaO, CaCl 2 and MgO to reduce fluoride is reported [27,28]. The samples on seventh day and 5 h showed the presence of calcium silicate hydrate and form of calcium hydroxide with similar 2θ values of 32.6 and 34.5, respectively.…”
Section: Mineralogical Characterization Of the Cement Samples In Colusupporting
confidence: 88%
“…Cement has calcium oxide and fluoride reacted with calcium to give calcium fluoride minerals. Similar studies are reported by earlier researchers where the potential of minerals such as CaO, CaCl 2 and MgO to reduce fluoride is reported [27,28]. The samples on seventh day and 5 h showed the presence of calcium silicate hydrate and form of calcium hydroxide with similar 2θ values of 32.6 and 34.5, respectively.…”
Section: Mineralogical Characterization Of the Cement Samples In Colusupporting
confidence: 88%
“…The ability of bone to defluoridate water was reported by Smith and Smith in 1937. 52 Different defluoridation techniques and the materials employed [37][38][39][40][41] impressive efficiency. [53][54][55] Bone char consists largely of hydroxyapatite and a significant amount of calcium carbonate while carbon accounts only for 10% (w/w).…”
Section: Mechanism Of Defluoridationmentioning
confidence: 99%
“…Groundwater containing high fluoride, which is a a worldwide phenomenon [2], will cause health problems [3]. Electrocoagulation is a suitable technique for defluoridization in rural area [3,4]. Zhou [5] analysed the water supply conditions in China and found that rural populations are vulnerable to water-related diseases due to lack of funds and monitor.…”
Section: Introductionmentioning
confidence: 99%